EFFECT OF RESPONSIBILITY ACCOUNTING APPLICATION AND STRATEGY IMPLEMENTATION TOWARD CORPORATE PERFORMANCE : (Case Study On PT. Clasies Star Probolinggo Branch Of Surabaya) - Diah Rani Nartasari (Fakultas Ekonomi Universitas 45 Surabaya, 2013)
In the current globalization era, many more business competition and the global economic situation was uncertain that requires management to be more active and more creative and able to cope problems that exist, so that the company can still go on to live and grown. Every company is required to have a differentiation advantages that can be used as an additional weapon to deal with competitors. That company's readiness to face the threats and challenges that will arise is through the formulation and implementation of appropriate strategies that align with the core excellence. The purpose of this study was to examine and analyze the relationship between the application of responsibility accounting and strategy implementation with corporate performance. The population of this study was all of branch manager of PT. CLASIES STAR PROBOLINGGO in Indonesia, amounted 130 peoples. The sampling technique was conducted with a